PDIA Toolkit - A DIY Approach to Solving Complex Problems - Samji, Salimah; Andrews, Matt; Pritchett, Lant; Woolcock, MIchael (Center for International Development at Harvard University, 2018)
The PDIAtoolkit is designed to guide you through the process of solvin g complex problems which requires working in teams. We call it a Do-it -Yourself (DIY) kit, where the ‘you’ is a committed team of 4-6 people mobilized to work together to solve a complex problem that cannot be solved by one person.